Short-period corrosion of X80 pipeline steel induced by AC current in acidic red soil. (November 2019) - Wei, Boxin; Qin, Qingyu; Bai, Yunlong; Yu, Changkun; Xu, Jin; Sun, Cheng; Ke, Wei
Abstract: Effect of alternating current (AC) on the corrosion behavior of X80 pipeline steel has been investigated using electrochemical techniques and surface analysis methods in real acidic red soils. The AC current dramatically enhances the corrosion of steel coupon, and the corrosion rate increases with the AC current density increasing. Compared with strong polarization curve, linear polarization curve is more suitable to evaluate the AC corrosion tendency of the steel coupon. The oxidizing effect of the AC current which acts as an oxidant increases the contents of ferric ions, which verifies the Faradaic rectification effect. Highlights: Alternating current (AC) induced corrosion of X80 pipeline steel was studied in real acidic red soils. AC current increases not only corrosion rate but also maximum pitting depth. Linear polarization is more suitable to evaluate variation tendency of AC corrosion. Variations of the corrosion product compositions verify the Faradaic rectification effect.